Haptic cueing modulates gait variability and is more user friendly than visual cues - Brink, Kolby J.; Haghighatnejad, Mehrnoush; Wiles, Tyler M.; Stergiou, Nick; Likens, Aaron D. (International journal of industrial ergonomics, 2025)
To compare visual versus haptic cueing modalities in modulating gait variability temporal structure using white noise, pink noise, and invariant interval patterns. Healthy human movement exhibits "pink noise" variability, representing optimal balance between stability and adaptability. Aging and pathology disrupt this pattern. While external cueing can help restore healthy patterns, visual and auditory approaches limit environmental awareness. Ten healthy young adults completed 12-min walking trials for each cueing condition across two counterbalanced sessions. Gait variability was quantified through Detrended Fluctuation Analysis (α) of inter-stride intervals. Synchronization accuracy between heel strikes and cues was measured as asynchrony. Usability was assessed using a modified System Usability Scale. Bayesian multilevel modeling showed noise condition significantly influenced α values, with white noise and invariant conditions reducing α values compared to control and pink noise conditions. Asynchrony values were not influenced by cueing type, modality, or session. Haptic cueing was strongly preferred over visual for frequent use (P = 0.985), reduced awkwardness (P = 0.996), and increased confidence (P = 0.996). Both modalities effectively modulated gait variability, with no differences in synchronization performance. However, haptic cueing received significantly higher usability ratings in key areas. Haptic cueing offers an effective alternative to visual cueing for gait rehabilitation, providing similar effectiveness while maintaining environmental awareness and better user experience, with potential applications through wearable technologies. •Haptic cueing effectively modulates gait variability similar to visual cueing.•Subjects consistently anticipate cues by ∼0.13 s regardless of cueing modality.•Haptic cueing received higher usability ratings for comfort, confidence, and desire for use.•Both modalities alter gait dynamics to match white noise, pink noise, and invariant patterns.•Haptic cueing offers advantages for real-world applications by maintaining environmental awareness.